STRATEGI PENGELOLAAN PERIKANAN BERKELANJUTAN PADA KAWASAN KONSERVASI PERAIRAN GITA NADA DI KABUPATEN LOMBOK BARAT: Strategy For Sustainable Fisheries Management In The Gitanada Marine Conservation Area In West Lombok Regency - Iman, Atifatul; Mulyawati, Sri; Husni, Syarif (Ganec Swara, 2025)
The development of marine conservation areas is one of the government's efforts to provide benefits and fairness to the community in terms of utilising fish resources through management activities in sustainable fishing zones to improve community welfare. However, communities still face challenges and issues in managing these conservation areas, such as overfishing by fishermen using dragnets, the capture of protected species, and destructive fishing activities by irresponsible individuals. Therefore, this study aims to develop strategies for sustainable fisheries management in the Gita Nada Marine Conservation Area. The methods used include SWOT analysis, beginning with an analysis of internal and external factors, as well as the development of a grand strategy matrix and a SWOT matrix. The results of this study recommend three alternative SO strategies based on the current conditions in the Gita Nada region, namely developing the use of effective and environmentally friendly fishing technologies such as the use of solar panels as a source of electricity, optimizing policies and programs as well as supporting institutions to increase production through community empowerment and guidance programs, and increasing the participation of fishermen in the development of conservation-based fisheries ecotourism by involving fishermen as management partners.